EXTENT OF UTILIZATION OF INTERACTIVE LEARNING PLATFORMS FOR ENHANCED ENGAGEMENT BY ECONOMICS EDUCATION STUDENT IN HIGHER INSTITUTIONS IN ENUGU STATE (NAU Journal of Technology and Vocational Education, 2026)
This study examined the extent to which interactive learning platforms are used to enhance student engagement in Economics Education in higher institutions in Enugu State. Three specific purposes and corresponding research questions guided the study. A descriptive survey design was adopted. The population comprised 24 Economics Education lecturers from two public institutions offering the programme in the state: University of Nigeria, Nsukka (13) and Federal College of Education, Ehamufu (11). Due to the small size, the entire population was studied using the census technique. Data were collected using a researcher-developed questionnaire titled Extent of Utilization of Interactive Learning Platforms for Enhanced Economics Education Student Engagement Questionnaire (EUILPEEESEQ). The instrument was validated by experts in Economics Education and Measurement and Evaluation. Reliability was established through a pilot test, yielding an overall coefficient of 0.79, indicating acceptable internal consistency. The instrument was administered with the support of two research assistants, and data were analyzed using mean and standard deviation to answer the research questions. Findings revealed that interactive learning platforms were utilized to a low extent for enhancing student engagement. Specifically, tools such as Zoom were underutilized in facilitating active learning. The study concluded that the low level of utilization of interactive platforms limits opportunities for improved student engagement in Economics Education. It was recommended that the National Universities Commission (NUC) should implement mandatory digital pedagogy training for lecturers to improve their effective use of interactive tools for teaching and learning.
Keywords: Economics Education; Interactive Learning Platform; Student Engagement; Utilization